Microbial Anti-Inflammatory Molecule (MAM) from Faecalibacterium prausnitzii Shows a Protective Effect on DNBS and DSS-Induced Colitis Model in Mice through Inhibition of NF-κB Pathway - Breyner, Natalia M.; Michon, Cristophe; de Sousa, Cassiana S.; Vilas Boas, Priscilla B.; Chain, Florian; Azevedo, Vasco A.; Langella, Philippe; Chatel, Jean M. (Frontiers in Microbiology, 2017)
Faecalibacterium prausnitzii and its supernatant showed protective effects in different chemically-induced colitis models in mice. Recently, we described 7 peptides found in the F. prausnitzii supernatant, all belonging to a protein called Microbial Anti-inflammatory Molecule (MAM). These peptides were able to inhibit NF-κB pathway in vitro and showed anti-inflammatory properties in vivo in a DiNitroBenzene Sulfate (DNBS)-induced colitis model. This current paper we tested MAM effect on NF-κB pathway in vivo, using a transgenic model of mice producing luciferase under the control of NF-κB promoter. Moreover, we tested this protein on Dextran Sodium Sulfate (DSS)-induced colitis in mice. To study the effect of MAM we orally administered to the mice a Lactococcus lactis strain carrying a plasmid containing the cDNA of MAM under the control of a eukaryotic promoter. L. lactis delivered plasmids in epithelial cells of the intestinal membrane allowing thus the production of MAM directly by host. We showed that MAM administration inhibits NF-κB pathway in vivo. We confirmed the anti-inflammatory properties of MAM in DNBS-induced colitis but also in DSS model. In DSS model MAM was able to inhibit Th1and Th17 immune response while in DNBS model MAM reduced Th1, Th2 and Th17 immune response and increased TGFβ production.